2008
DOI: 10.1128/jb.00088-08
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Gene Expression in a Mixed-Genus Community: Stabilized Arginine Biosynthesis inStreptococcus gordoniiby Coaggregation withActinomyces naeslundii

Abstract: Interactions involving genetically distinct bacteria, for example, between oral streptococci and actinomyces, are central to dental plaque development. A DNA microarray identified Streptococcus gordonii genes regulated in response to coaggregation with Actinomyces naeslundii. The expression of 23 genes changed >3-fold in coaggregates, including that of 9 genes involved in arginine biosynthesis and transport. The capacity of S. gordonii to synthesize arginine was assessed using a chemically defined growth mediu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
119
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(126 citation statements)
references
References 61 publications
4
119
1
2
Order By: Relevance
“…Jakubovics et al have used DNA microarray to systematic search Streptococcus gordonii (S. gordonii) genes regulated in response to coaggregation with A. naeslundii in multi-species dental plague biofilm. In this study, they found that 9 S. gordonii genes involved in arginine biosynthesis and transport are highly induced in coaggregates, but not in co-cultures with A. naeslundii, which enables aerobic S. gordonii growth when exogenous arginine is limited [49]. Wen et al reported that expression of Streptococcus mutans (S. mutans) virulence genes is significantly reduced in multi-species biofilms with S. oralis or Lactobacillus casei [50].…”
Section: Interactions In Multi-species Biofilmsmentioning
confidence: 96%
“…Jakubovics et al have used DNA microarray to systematic search Streptococcus gordonii (S. gordonii) genes regulated in response to coaggregation with A. naeslundii in multi-species dental plague biofilm. In this study, they found that 9 S. gordonii genes involved in arginine biosynthesis and transport are highly induced in coaggregates, but not in co-cultures with A. naeslundii, which enables aerobic S. gordonii growth when exogenous arginine is limited [49]. Wen et al reported that expression of Streptococcus mutans (S. mutans) virulence genes is significantly reduced in multi-species biofilms with S. oralis or Lactobacillus casei [50].…”
Section: Interactions In Multi-species Biofilmsmentioning
confidence: 96%
“…It is noteworthy that P. gingivalis and F. alocis interspecies interaction resulted in the up-regulation of arginine deiminase (HMPREF_0389_01584) and carbamate kinase (HMPREF_0389_00535) in F. alocis (unpublished observations). While it may use a novel arginine catabolic pathway compared with other AAGPRs in the periodontal pocket (Uematsu et al, 2003), its relative abundance in the periodontal pocket and its enhanced ability to produce ammonia could promote species co-habitation and survival (Jakubovics et al, 2008). Because butyrate is a metabolic end-product from arginine, it could likely also have an impact on other microbial interactions, including viruses, in the oral cavity.…”
Section: Proteome Associated With Microbe-host Interactionmentioning
confidence: 99%
“…In the presence of A. naeslundii, S. gordonii can grow under arginine depletion conditions in which S. gordonii usually does not survive. 93,94 Veillonella. Veillonella species can produce vitamin K, which can be utilized by Prevotella spp and Porphyromonas spp for their growth.…”
mentioning
confidence: 99%